D‐Carvone inhibits the JAK/STAT3 signaling pathway and induced the apoptotic cell death in the human gastric cancer AGS cells. Issue 5 (4th March 2021) - Lv, Long; Yang, Nan; Cao, Youhong; Dang, Junqiang; Cheng, Likun; El‐Sheikh, Mohamed A.; Zhang, Yun
Abstract: Globally, gastric cancer is one of the leading cause of death. Surgical and chemotherapy constitute an important treatment regimen. Unfortunately, less than 20 persons out of 100 patients are live on almost 5 years. Hence, a nontoxic, effective and significantly enhancing novel therapeutic agent is required. d ‐Carvone is a natural terpenoid present in the essential oils and abundant in the seeds of caraway, as well as known folk medication for diarrhea, acidity, and other gastric disorders. Nevertheless, the role of d ‐carvone on gastric cancer and its underlying molecular mechanism resides enigmatic. Cells were treated with d ‐carvone to find out the IC50 by MTT assay. This study shows that 20 and 25 μM d ‐carvone has induced the reactive oxygen species production and mitochondrial membrane potential in gastric cancer AGS cells, which were evaluated by 2, 7‐dichlorofluoresceindiacetate and Rh123 staining methods, respectively. The effect of d ‐carvone against the Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathway was studied through immunoblotting. Then, we found that it effectively inhibited the proliferation of cell, and the induction of cell apoptosis was scrutinized by dual, 4', 6‐diamidino‐2‐phenylindole, and also propidium iodide staining methods. We also explored the fundamental molecular signaling mechanism of the d ‐carvone and our data depicts that d ‐carvone induced apoptosis cell death by mitochondrial reactive oxygen species production and downregulation of the and JAK and STAT3 signaling molecules. These overall findings support that the d ‐carvone inhibits the JAK/STAT3 signaling pathway and induces cell death in the gastric cancer AGS cells.